2020
DOI: 10.14716/ijtech.v11i2.3225
|View full text |Cite
|
Sign up to set email alerts
|

Mini-electronic Tongue Used to Discriminate between Coffee Samples of Different Geographical Origin

Abstract: This paper presents a mini-electronic tongue that used a polymeric sensor array made from polypyrrole to discriminate between coffee samples of different geographical origin. The electronic tongue consisted of a system with a voltammetric sensor array coupled to a multichannel measuring device (multi-potentiostat) that was controlled by a multivariable data collection and processing application. The samples analyzed comprised two types: a series of substances with different chemical and taste properties and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Numerous studies have shown the importance of the geographical origin in conferring distinctive quality attributes to the coffee; notwithstanding, traditional techniques of determining this criterion are quite cumbersome. Alternatively, the authors of [ 234 ] attempted to determine the geographical groups of Arabica coffees from Colombia using a mini E-tongue comprising a polymeric sensor array with PPy modified using different counter ions. The acquired results showed the capability of the mini-E-tongue for the geographical based separation of the different coffee samples using PCA.…”
Section: Electronic Tongue: Historical Background and Food Qualitymentioning
confidence: 99%
“…Numerous studies have shown the importance of the geographical origin in conferring distinctive quality attributes to the coffee; notwithstanding, traditional techniques of determining this criterion are quite cumbersome. Alternatively, the authors of [ 234 ] attempted to determine the geographical groups of Arabica coffees from Colombia using a mini E-tongue comprising a polymeric sensor array with PPy modified using different counter ions. The acquired results showed the capability of the mini-E-tongue for the geographical based separation of the different coffee samples using PCA.…”
Section: Electronic Tongue: Historical Background and Food Qualitymentioning
confidence: 99%
“…This type of device operates on systems comprised of three major components: a sensor array with cross selectivity, an electronic multichannel measurement device, and a data analysis unit utilizing multivariate or pattern recognition techniques (Vlasov et al, 2005). The electronic tongue devices developed were based on different analytical principles, and various sensor arrays have been used (Arrieta et al, 2020;Facure et al, 2020;Zabadaj et al, 2018;Lipkowitz et al, 2018). However, electronic tongues based on electrochemical measurements have received widespread acceptance from the scientific community and the industry, particularly those based on potentiometric and voltammetric sensor arrays (Arrieta et al, 2020;Oroian and Ropciuc, 2019;Lipkowitz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The electronic tongue devices developed were based on different analytical principles, and various sensor arrays have been used (Arrieta et al, 2020;Facure et al, 2020;Zabadaj et al, 2018;Lipkowitz et al, 2018). However, electronic tongues based on electrochemical measurements have received widespread acceptance from the scientific community and the industry, particularly those based on potentiometric and voltammetric sensor arrays (Arrieta et al, 2020;Oroian and Ropciuc, 2019;Lipkowitz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed head-to-head comparison of some of these instruments and their applications have been reported [ 5 , 9 , 20 , 26 ] but this current study will focus solely on the e- tongue. Ideally, the e-tongue is better suited for liquid samples and combination with chemometric techniques, it has been used to monitor the quality of coffee [ 27 ], wine [ 24 , 28 , 29 ], fruit juice [ 24 ], oils [ 25 , 30 , 31 ], tea [ 32 ], and recently in some semi-solid foods like tomato concentrate [ 33 ]. With mathematical correction methods [ 28 , 29 , 32 , 34 ], signals from the e-tongue sensors can be further optimized to compensate for issues of drift that could arise from environmental factors, such as temperature, relative humidity, etc., or sensor aging [ 5 , 20 , 28 ].…”
Section: Introductionmentioning
confidence: 99%